MOTHERS OF GREAT PEOPLE - Yunusova G.S (International Journal of Literature and Language Studies, 2026)
Abstract:This article presents an analytical study of the mothers of great figures who left an enduring mark on the history of the peoples of Central Asia. In particular, it examines the role of Amir Temur’s mother and wives in state governance, as well as their contribution to the education of princes through the implementation of a just and effective style of leadership.